Shift-modulation invariant spaces on LCA groups - Cabrelli, Carlos (2012)
A (K,Λ) shift-modulation invariant space is a subspace of L2(G) that is invariant under translations along elements in K and modulations by elements in Λ. Here G is a locally compact abelian group, and K and Λ are closed subgroups of G and the dual group Gˆ, respectively. We provide a characterization of shift-modulation invariant spaces when K and Λ are uniform lattices. This extends previous results known for L2(Rd). We develop fiberization techniques and suitable range functions adapted to LCA groups needed to provide the desired characterization.